The Use of DOACs in Pediatrics: Current Therapeutic and Prophylactic Indications, Cardiac Indications, and Real-World Evidence—A Review - Bosch, Alessandra; Olivieri, Martin; Holzhauer, Susanne (Hämostaseologie, 2025)
Based on clinical trials that have been conducted and published in the past decade, direct oral anticoagulants (DOACs) are increasingly being used as an antithrombotic treatment in children with venous thrombotic events and to prevent thrombotic events in children at risk. In this review, current indications and standards for the initiation of DOACs in children are summarized for the treatment of venous thrombotic events and for the primary and secondary prevention in children at risk of developing thromboses based on the published randomized controlled trials (RCT). Similarly, indications for DOACs in children with underlying cardiac disease are portrayed based on RCT findings. Lastly, available real-world data are reviewed for the use of DOACs in pediatric patients with a focus on patients at higher risk of both thrombosis and bleeding who were primarily excluded from the RCTs. DOACs contribute largely to the evolving individualization of care of thrombotic events in children, but at-risk patient populations remain underrepresented regarding DOAC experience, such as preterm infants, and children with severe renal or hepatic disease. Real-world data from observational studies and registries will continue to be necessary to establish DOACs' effectiveness and safety in children in everyday clinical use.
Keywords: DOAC; pediatrics; heart disease; VTE treatment; thromboprophylaxis